Learners' perspectives on the prevention and management of pregnancy school dropout: a Namibian case - Shiningayamwe, Dorthea Nanghali Etuwete (Frontiers in Sociology, 2023)
This study investigated the learners' perspectives on preventing and managing pregnancy and school dropout regarding the Namibia education sector policy on preventing and managing learner pregnancy. The study conducted seventeen individual and ten focus group interviews with 63 school-going learners, including adolescents, pregnant and learner parents. Using the phenomenological data analysis framework, learner perspectives show factors driving learner pregnancy and school dropout, such as older men and cattle herders preying on girls, long school holidays, alcohol sites near school premises and age restrictions. The proposed learner-focused interventions include prohibiting learners' access to cuca shops and shebeens, reinforcing stakeholder collaborations, sensitising girls and cattle herders, and ongoing advocacy. The study highlights the importance of incorporating learners' perspectives in policy interventions as valuable insights for reducing learner pregnancy and school dropout in rural Namibian schools.